La Déclaration des droits de la femme et de la citoyenne d'Olympe de Gouges (1791): Une femme entre semi-fiction et dogme politique. Issue 3 (December 2019) - VIGUIER, AUDREY
Abstract : This article deconstructs the legal semi-fiction written by Olympe de Gouges: The Declaration of the Rights of Women (1791). Using the French discourse analysis software TROPES, it examines the universe, actors and semantic relations that compose this legislative simulacrum around the notions of women and citizenship . Between the ideal and the real, Olympe de Gouges introduces multiple conscious faults to create a fictional "as if" scenario (Hans Vaihinger) with the ultimate goal of transforming her semi-fiction into political dogma.